Travel hurdles and dark tourism destinations: Unraveling Malaysian tourists’ visit intentions - Saad, Mazni; Murad, Nur Farradilla; Kassim, Normalini Md; Ahmad, Aznita (Turyzm/Tourism, 2025)
Dark tourism is associated with death and tragedy, and these sites attract visitors for education, leisure and historical interest with motivations including media portrayals and amusement. The research explores visitor motivations and emotional experiences in Malaysia, aiming to understand travel constraints and enhance awareness and interest, addressing gaps in local literature and practical strategies. Dark tourism in Malaysia needs more marketing and higher awareness. Despite its potential, it fails to attract tourists due to inadequate promotion and the need for more attention from authorities, industry growth is hindered. A quantitative study using a self-administered survey targeting visitors and non-visitors to dark tourism sites in Malaysia, employed non-probability and purposive sampling. One hundred and fifty data sets were collected from Google Forms distributed through WhatsApp and Twitter for one month. Though the theory of reasoned action confirmed the structural model, the results show that all three hypotheses are rejected. This indicates that the underlying reasons based on the results need further investigation.